Glioblastoma, IDH-Wildtype With Epithelioid Morphology and a BCR::NTRK2 Fusion - Umeres-Francia, Gianfranco E. (2024)
Glioblastoma, IDH-wildtype (GBM) is a high-grade astrocytic glioma that accounts for the majority of malignant brain tumors in adults. Within this entity, epithelioid GBM represents a histological subtype characterized by a loosely cohesive aggregate of large cells with abundant cytoplasm, and vesicular nuclei that usually harbors the BRAF V600E mutation. Molecular alterations in GBMs are frequent and play an important role in the diagnosis of this entity. Among the many genetic alterations reported, NTRK fusions are rare and account for <2% of gliomas. Furthermore, NTRK2 fusions are most seen in pediatric populations. Recent approval of the TRK inhibitor larotrectinib by the Food and Drug Administration (FDA) has brought interest in the study and recognition of NTRK fusions in multiple types of tumors. Trials that assess the response to this drug in cancers carrying NTRK fusions have yielded favorable results. We discuss a rare presentation of an adult-type GBM with epithelioid morphology and a BCR::NTRK2 gene fusion.